2016
DOI: 10.2169/internalmedicine.55.6301
|View full text |Cite
|
Sign up to set email alerts
|

Urinary β-2 Microglobulin Levels Sensitively Altered in an Osteomalacia Patient Receiving Add-on Adefovir Dipivoxil Therapy for Hepatitis B Virus Infection

Abstract: Adefovir dipivoxil (ADV) is effective for hepatitis B virus (HBV) infection; however, ADV may provoke renal injury resulting in osteomalacia, and this side effect is seldom recognized until bone fractures emerge. We herein present a 66-year-old woman with HBV infection who received ADV for 6 years. Although she exhibited no sign of bone fractures, her urinary β-2 microglobulin (β2MG) level increased to 83,837 μg/L and scintigraphy revealed minimal fractures of the third rib. ADV was subsequently reduced and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…After cessation of ADV and long-term follow-up, patient 1 and patient 4 were still found to have high urine β 2 -MG levels. Urine β 2 -MG is a sensitive marker of renal tubular injury 17,18. This indicated that proximal renal tubular function could not be completely restored in patient 1 and patient 4.…”
Section: Discussionmentioning
confidence: 98%
“…After cessation of ADV and long-term follow-up, patient 1 and patient 4 were still found to have high urine β 2 -MG levels. Urine β 2 -MG is a sensitive marker of renal tubular injury 17,18. This indicated that proximal renal tubular function could not be completely restored in patient 1 and patient 4.…”
Section: Discussionmentioning
confidence: 98%
“…The urinary β2-microglobulin level has been suggested to be a biomarker of kidney injury among chronic HBV patients treated with low-dose ADV (24). Takagi et al reported the sensitive change in the urinary β2-microglobulin level after dose reduction of ADV (25). Thus, a careful evaluation of the urinary β2-microglobulin level is mandatory for the early recognition of ADV-induced tubular damage.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that β2-microglobulin is detected clearly in patients with ADV-induced hypophosphatemic osteoporosis, and hence can be used as an indicator of renal function in these particular patients. 18 …”
Section: Discussionmentioning
confidence: 99%